Movable Fluid Distribution Characteristics and Microscopic Mechanism of Tight Reservoir in Yanchang Formation, Ordos Basin - Wu, Ke; Chen, Dezhao; Zhang, Weigang; Yang, Hua; Wu, Hanning; Cheng, Xin; Qu, Yiqian; He, Mengqing (Frontiers in Earth Science, 2022)
Tight sandstone reservoirs have smaller pore throats, complex structures, strong heterogeneity in the pore throat system, and significant differences in fluid distribution. To reveal the occurrence characteristics of movable fluids in tight sandstone reservoirs, a typical tight sandstone core sample from the Chang 4+5 reservoir in the Tiebiancheng area of the Ordos Basin was selected and established using casting thin slices, field emission scanning electron microscopy (FE-SEM), high-pressure mercury injection (HPMI), and nuclear magnetic resonance (NMR) technology classification criteria for microscopic pore throats of target reservoirs. The test analysis results showed that the pore throat structure of the Chang 4+5 tight sandstone reservoir in the Tiebiancheng area can be divided into Type I, II, and III reservoirs. Type I reservoirs have well-developed pore throats, good connectivity, low displacement pressure (0.42 MPa on average), high movable fluid saturation (46.82% on average), and a minimum pore throat radius of movable fluid (0.056 μm on average). The pore throat structure and fluid production degree of the other two reservoir types gradually deteriorated. Note that the tight sandstone reservoirs of the Chang 4+5 oil layer group have smaller pore throats but high movable fluid content in smaller pore throats. With the deterioration of the reservoir’s pore throat structure, the degree of fluid utilization in larger pore throats decreases, whereas the degree of fluid utilization in smaller pore throats does not change significantly. Many factors affect movable fluid parameters. The movable fluid parameters of tight sandstone reservoirs in the Chang 4+5 oil layer group in the Tiebiancheng area have a good positive correlation with permeability and sorting coefficients. The movable fluid parameters of smaller and larger pore throats have no obvious correlation with a single factor. Multiple factors affect the fluid occurrence characteristics of different scale pore throats.